2019
DOI: 10.1002/cphc.201801085
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Excited‐State Proton‐Transfer Dynamics inside the Nanocavity of Microheterogeneous Systems: Microenvironment‐Sensitive Förster Energy Transfer to Riboflavin

Abstract: The excited‐state proton‐transfer efficiency of a tetraarylpyrene derivative, 1,3,6,8‐tetrakis(4‐hydroxy‐2,6‐dimethylphenyl)pyrene (TDMPP), was investigated thoroughly in the presence of various surfactant assemblies, such as micelles and vesicles. The confined microheterogeneous environments can significantly retard the extent of the excited‐state proton‐transfer process, resulting in a distinguishable optical signal compared to that in the bulk medium. Physical characteristics of the surfactant assemblies, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…33−35 Pyrene has been chosen as the fluorophore of interest due to notable characteristics, including large photostability, long fluorescence decay time, and a propensity to dimerize and self-associate (formation of excimers). 36,37 However, the possible photoinduced electron transfer from the pyrenylic nitrogen (PyCH 2 -N) to the excited pyrenyl (Py*) chromophore is expected to lead to a quenching of emission since the deactivation of the excited state will proceed through a radiationless process. 38 However, owing to three primary nitrogen centers, bpa-based fluorescence probes have often been employed in constructing several sensors for transition metal ions and pH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33−35 Pyrene has been chosen as the fluorophore of interest due to notable characteristics, including large photostability, long fluorescence decay time, and a propensity to dimerize and self-associate (formation of excimers). 36,37 However, the possible photoinduced electron transfer from the pyrenylic nitrogen (PyCH 2 -N) to the excited pyrenyl (Py*) chromophore is expected to lead to a quenching of emission since the deactivation of the excited state will proceed through a radiationless process. 38 However, owing to three primary nitrogen centers, bpa-based fluorescence probes have often been employed in constructing several sensors for transition metal ions and pH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The molecule under consideration here is a bifunctional PET sensor, (1-pyrenyl)­methyl-bis-[(2-pyridyl)­methyl]­amine ( Pybpa ), composed of two distinct modules, bispicolyl as a binding site and pyrene as the signaling moiety. The compound was synthesized in a facile manner by coupling pyrenylmethyl chloride with the metal ion binding bis-[(2-pyridyl)­methyl]­amine ( bpa ) unit. Pyrene has been chosen as the fluorophore of interest due to notable characteristics, including large photostability, long fluorescence decay time, and a propensity to dimerize and self-associate (formation of excimers). , However, the possible photoinduced electron transfer from the pyrenylic nitrogen (PyCH 2 - N ) to the excited pyrenyl (Py*) chromophore is expected to lead to a quenching of emission since the deactivation of the excited state will proceed through a radiationless process . However, owing to three primary nitrogen centers, bpa -based fluorescence probes have often been employed in constructing several sensors for transition metal ions and pH. , Such recovery of fluorescence signal via metal ion/ H + coordination is often termed chelation-enhanced fluorescence (CHEF).…”
Section: Resultsmentioning
confidence: 99%
“…[14] Thus, at this condition, we can expect formation of micellar structures, where the central hydrocarbon core is surrounded by stern layer (for ionic micelles) or palisade layer (for neutral micelles) containing head group of the surfactants and tightly-bound water molecules. [15] At pH 7.4, compound 1 showed orange color both in buffered medium and in presence of neutral and/or cationic micelles. However, the color changed to red in the presence of anionic micelle.…”
Section: Optical Response Of Probe Molecule Towards Local Ph At the I...mentioning
confidence: 96%
“…The red-shi phenomenon suggested that the probe was susceptible to intramolecular charge transfer when bound to Cu 2+ , and the appearance of absorption bands at 500 nm and 520 nm may be attributed to intramolecular charge transfer interactions. [49][50][51] As the concentration of Cu 2+ increases, the uorescence intensity at 500 nm slowly decreased and CCU was dynamically responsive to the concentrations of Cu 2+ in the…”
Section: Spectrophotometric Experiments On Ccumentioning
confidence: 99%